How the market for standards shapes competition in the market for goods: Sustainability standards in the cut flower industry - Lone Riisgaard (Danish Institute for International Studies (DIIS), 2009)
Sustainability initiatives have proliferated in many industries in recent years. This has led to a plethora of standards that exist in parallel to each other seeking to address more or less the same social and environmental issues. Sustainability standards are not neutral tools but institutional mechanisms that differ in the way they seek to implement their objectives and in the impact they have on intended beneficiaries and other value chain actors. In this paper I explore the emergence of multiple standards seeking to regulate the social conditions in the production of cut flowers aimed at the EU market. I investigate developments in the focus and function of these standards and the effect of standards and standard harmonization attempts on the terms of competition in the cut flower value chain. The analysis shows that the harmonization of flower standards has a potential to 'lift the standard bar' by transforming risk management standards into product differ-entiation standards. The paper also shows how the market for standards can shape competition in the market for flowers by altering the terms of participation in the growing market segment for 'sustainable' flowers. Through the new standard harmonization initiative Fair Flowers Fair Plants, Dutch growers are now able to compete in the market for socially labelled flowers which before was restricted to Southern producers.
Keywords: 330; Zierpflanzenbau; Internationale Sozialstandards; Nachhaltige Entwicklung; Wettbewerb